Model Pembelajaran Digital Berbasis Riset di Perguruan Tinggi - Abdul Halik; St Wardah Hanafie; Ahmad S Rustan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to determine the transition from conventional learning to digital learning. The research method is Research and Development carried out at IAIN Parepare. The research stages start from FGD, product design, expert validation, product testing, verification, publication and implementation. This research shows that research-based digital learning is very important and must be implemented. Research-based digital learning utilizes digital features in creating content, research as a strategy in implementing learning. The results of the research are made up of content as teaching materials, then setting the evaluation system in the form of assessment tools. Digital collaboration and research in learning can accommodate student learning styles that are independent, thorough, inquiry, problem solving, contextual, authentic, and collaborative